PENGARUH KUALITAS PERGURUAN TINGGI, LOKASI DAN BIAYA TERHADAP KEPUTUSAN KULIAH DI IAIN SURAKARTA - Hapsari Nawaningsih; Eny Kustiyah; Ida Aryati (ITB AAS INDONESIA Surakarta, 2019)
This study aims to determine and explain the effects of both the simultaneous and partial quality of tertiary institutions, locations and costs on college decisions at IAIN Surakarta. Type of quantitative research, the source of the data comes from respondents (Primary Data) and from Surakarta IAIN documents (Secondary Data). This study took the population of 2018 semester 2 students of IAIN Surakarta and a sample of 100 people taken randomly from all faculties (Random Sampling). Data analysis uses multiple linear regression analysis. The results of this study indicate that the quality of tertiary institutions, location and cost have a simultaneous and significant effect on college decisions at IAIN Surakarta as evidenced by the Sig 0,000 and Fcount of 28,984. In the t test of quality, location and cost have a positive and significant effect on college decisions at IAIN Surakarta with a quality value of Sig 0,000 and tcount of 4,627, location values of Sig 0,001 and tcount of 3,541 and cost of Sig of 0.009 and tcount of 2,667. Based on the coefficient of determination test contributed 45.9% to the decision of college at IAIN Surakarta while the rest are other factors outside this study. Keywords: quality, location, costs and college decisions